The professional performance in the nursing prenatal assistance - Moura, Escolástica Rejane Ferreira; Rodrigues, Maria do Socorro Pereira (Rev Rene, 2002)
The present work avaliates nurses’ performances in the prenatal assistance, in the health of a very smol of Ceará State (Baturité). Data were collected, in 1999, in the June (04 municipal districts) and 2000, in February (04 municipal districts). The sample was constituted of eight nurses (01 from each municipal district) and twenty-four consultations were observed. We used the participant observation, as research method. The result demonstrated a good nursing performance; Is mode us recognize those professionals’ great contribution to the binomial mother/child health. However, it was verified an absence of the nursing systematic assistance.